2009
DOI: 10.1038/cdd.2009.26
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of faim reveals its role in modulating c-FLIP expression during CD95-mediated apoptosis of lymphocytes and hepatocytes

Abstract: Fas-apoptosis inhibitory molecule (FAIM) is inducibly expressed in B lymphocytes and had been shown to antagonize Fas-mediated killing of B-cell lines in vitro. However, its mechanism and role in vivo are unknown. We have generated faim À/À mice and found these mutants to be viable. In contrast to fas À/À mice, faim À/À mice have normal B-and T-cell populations. However, faim À/À B cells and thymocytes show increased sensitivity to Fas-triggered apoptosis in vitro, and faim À/À mice suffer greater mortality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…Subsequently, it was also shown to play a role in NF-B activation during neurite outgrowth (25). We also recently demonstrated that it played a role in Fas-triggered apoptosis of lymphocytes and hepatocytes (27). In this report, we further demonstrate a role for FAIM in TCR-mediated apoptosis of thymocytes using cells with loss and gain of function of FAIM.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Subsequently, it was also shown to play a role in NF-B activation during neurite outgrowth (25). We also recently demonstrated that it played a role in Fas-triggered apoptosis of lymphocytes and hepatocytes (27). In this report, we further demonstrate a role for FAIM in TCR-mediated apoptosis of thymocytes using cells with loss and gain of function of FAIM.…”
Section: Discussionmentioning
confidence: 49%
“…Induced by TCR Stimulation and Inhibits TCR-mediated Apoptosis of Thymocytes-As FAIM is induced by antigen receptor stimulation in B cells (24,27), we examined whether TCR cross-linking could up-regulate FAIM expression in thymocytes. WT thymocytes expressed a basal level of FAIM ex vivo, and we noticed an increase in FAIM protein levels in these cells following an 18-h treatment with a high dose (10 g/ml) of anti-CD3 and anti-CD28 (1 g/ml) antibodies (Fig.…”
Section: Faim Ismentioning
confidence: 99%
See 2 more Smart Citations
“…Caspase-8 is active in medullary, semimature heat-stable antigen hi SP thymocytes as a consequence of strong TCR stimulation. The death receptors-Fas, FADD, Fas apoptotic inhibitory molecule (Huo et al, 2009), and FADD-like IL1b-converting enzyme inhibitory protein (FLIP)-are involved upstream of caspase-8 activation, whereas BH3 interacting domain death agonist (Bid) and HDAC7 are activated downstream. Finally, caspase-8 has been linked to the protein glucocorticoid-induced leucine zipper (Gilz) in mediating glucocorticoid-induced thymocyte apoptosis (Pozzesi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%